1978
DOI: 10.1021/bi00610a031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the estradiol receptor extracted from nuclei by micrococcal nuclease

Abstract: The estradiol receptor of lamb endometrium, translocated to nuclei in útero and extracted with micrococcal nuclease at 2-4 °C, was compared under low salt conditions to the "native" 8S and to partially proteolyzed cytosol receptor.The degree of extraction of the receptor was roughly parallel to the proportion of digested chromatin and to the yield of extracted DNA. After extensive digestion of chromatin, which produced up to 10% perchloric acid soluble DNA and more nucleosome monomer than dimer, up to 80% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…It was found to have a single subunit with a molecular weight of 70,000, sedimenting at 8S. Rochefort and co-workers (94) found that the 4-6S nuclear receptor of lamb uterus could be dissociated by KC1 into 3.8S forms and yielded two hormone binding peaks on DEAE-cellulose.…”
Section: B Specific Examples 1 Progesterone Receptormentioning
confidence: 99%
“…It was found to have a single subunit with a molecular weight of 70,000, sedimenting at 8S. Rochefort and co-workers (94) found that the 4-6S nuclear receptor of lamb uterus could be dissociated by KC1 into 3.8S forms and yielded two hormone binding peaks on DEAE-cellulose.…”
Section: B Specific Examples 1 Progesterone Receptormentioning
confidence: 99%
“…Recently, attempts to characterize the intranuclear localization sites by application of nuclease digestion have gained momentum (Mainwaring, 1975;Hemminki & Vauhkonen, 1977;Andre, Raynaud & Rochefort, 1978;Massol, Lebeau & Baulieu, 1978;Senior & Frankel, 1978; Alberga, Tran & Baulieu, 1979; Rennie, 1979; Davies, Thomas, Borthwick & Giles, 1980;Scott & Frankel, 1980;Bruchovsky, Rennie & Comeau, 1981;Schoenberg & Clark, 1981;Davies, Thomas & Giles, 1982; Pavlik & Katzenellenbogen, 1982). The combination of nuclease digestion and salt extraction has contributed largely to the assignment of steroid receptor-binding sites to two nuclear 'areas', the chromatin domains and the nuclear matrix (Barrack et al 1977(Barrack et al , 1979; Barrack & Coffey, 1980.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was reported that estrogen treatment (and, therefore, the presence of hormone-receptor complexes in nuclei) enhances the overall sensitivity to DNase I of the genome (Senior and Frankel, 1978) as well as specifically of that of the ovalbumin gene (Garel and Axel, 1976;Weintraub and Groudine, 1976;. Micrococcal nuclease has also been reported to preferentially release from chromatin the nuclear receptor for estrogen (Andre et at., 1978(Andre et at., , 1980 and thyroid hormone (Gardner, 1978). Again, of course, the starting materials are complex and poorly characterized, and the results therefore difficult to interpret.…”
Section: The Rote Of Nuclear Receptors In Transcriptionmentioning
confidence: 99%